2005
DOI: 10.1007/s10350-004-0747-0
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 Alleles May Influence Disease Phenotype in Patients With Inflammatory Bowel Disease: A Critical Reappraisal With Review of the Literature

Abstract: Some clinical features of Crohn's disease and ulcerative colitis may be influenced by specific HLA-DR alleles; in particular, in ulcerative colitis some alleles appear to segregate with more aggressive disease, whereas in Crohn's disease different alleles cosegregate in patients with colonic disease and extraintestinal manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
0
21
1
2
Order By: Relevance
“…A meta-analysis of all genetic linkage studies was published in 2004, confirming the relationship between IBD and HLA molecules [17]. Previous studies have shown a link of HLA class II to UC and CD, revealing a possible connection between DR13 with UC and DR3 with DC [18]. A recent publication further suggests a possible increased risk of developing colorectal cancer in those who have UC and carry DR17 [19].…”
Section: Introductionmentioning
confidence: 85%
“…A meta-analysis of all genetic linkage studies was published in 2004, confirming the relationship between IBD and HLA molecules [17]. Previous studies have shown a link of HLA class II to UC and CD, revealing a possible connection between DR13 with UC and DR3 with DC [18]. A recent publication further suggests a possible increased risk of developing colorectal cancer in those who have UC and carry DR17 [19].…”
Section: Introductionmentioning
confidence: 85%
“…In a German study, the rs7574865 SNP in the STAT4 gene was associated with colonic CD 19 . The HLA-DRB1 (DR3) allele has been associated with colonic CD (11.5% vs. 0.4%) 20 while the TNF receptor superfamily polymorphism TNFRSF1B was inversely associated with colonic involvement independent of NOD2 21 . Homozygosity for the TCF4 transcription factor in the Wnt pathway 17 and NOD2 (Leu1007fsX1008) homozygosity have been associated upper gastrointestinal involvement in CD while a promoter region polymorphism in the macrophage migration inhibitor factor ( MIF ) appears to confer protection against upper gut involvement 22 .…”
Section: Genotype-phenotype Correlations In Ibdmentioning
confidence: 99%
“…The human leukocyte antigen (HLA) haplotype DRB1 was reported to be the most frequent in both diseases [9,10]. Furthermore, increases in interleukin (IL)-12 and IL-6 were noted in the two diseases, suggesting that similar proinflammatory cytokines are commonly involved in the pathogenesis of both diseases [11,12].…”
Section: Discussionmentioning
confidence: 97%